Long-term efficacy and safety of fostemsavir among subgroups of heavily treatment-experienced adults with HIV-1. (1st June 2021) - Ackerman, Peter; Thompson, Melanie; Molina, Jean-Michel; Aberg, Judith; Cassetti, Isabel; Kozal, Michael; Castagna, Antonella; Martins, Marcelo; Ramgopal, Moti; Sprinz, Eduardo; Treviño-Pérez, Sandra; Streinu-Cercel, Adrian; et al.
Abstract : Objectives: The aim of this study was to understand how demographic and treatment-related factors impact responses to fostemsavir-based regimens. Design: BRIGHTE is an ongoing phase 3 study evaluating twice-daily fostemsavir 600 mg and optimized background therapy (OBT) in heavily treatment-experienced individuals failing antiretroviral therapy with limited treatment options (Randomized Cohort 1-2 and Nonrandomized Cohort 0 fully active antiretroviral classes). Methods: Virologic response rates (HIV-1 RNA <40 copies/ml, Snapshot analysis) and CD4 + T-cell count increases in the Randomized Cohort were analysed by prespecified baseline characteristics (age, race, sex, region, HIV-1 RNA, CD4 + T-cell count) and viral susceptibility to OBT. Safety results were analysed by baseline characteristics for combined cohorts (post hoc). Results: In the Randomized Cohort, virologic response rates increased between Weeks 24 and 96 across most subgroups. Virologic response rates over time were most clearly associated with overall susceptibility scores for new OBT agents (OSS-new). CD4 + T-cell count increases were comparable across subgroups. Participants with baseline CD4 + T-cell counts less than 20 cells/μl had a mean increase of 240 cells/μl. In the safety population, more participants with baseline CD4 + T-cell counts less than 20 vs. at least 200 cells/μl had grade 3/4 adverse events [53/107 (50%) vs. 24/96 (25%)], serious adverse events [58/107 (54%) vs. 25/96 (26%)] and deaths [16/107 (15%) vs. 2/96 (2%)]. There were no safety differences by other subgroups. Conclusion: Week 96 results for BRIGHTE demonstrate comparable rates of virologic and immunologic response (Randomized Cohort) and safety (combined cohorts) across subgroups. OSS-new is an important consideration when constructing optimized antiretroviral regimens for heavily treatment-experienced individuals with limited remaining treatment options. Abstract : Supplemental Digital Content is available in the text